Sexual Satisfaction and its Relation to Marital Happiness in Iranians - A Rahmani; E Merghati Khoei; L Alah Gholi (Tehran University of Medical Sciences, 2009)
Background: Marital satisfaction is affected by many factors. Satisfaction with one's sexual life tends to be a pivotal factor in marital satisfaction. In Iran, Socio-cultural and political limitations are obstacles for sexuality-related studies, therefore, insufficient information is available in the area. Unique in its own, in this paper we report how sexual relationships relate to marital satisfaction among Iranians. Methods: This descriptive-correlation study was conducted in 2007 in Tehran, continuous sampling was used to recruit 292 married men, and women aged 19-58 yr from selected hospitals in Tehran while visiting their hospitalized relatives. Sometimes the participants were couple too. Three questionnaires were used for data collection. The data were analyzed using descriptive and inferential statistics (x2، Fisher and Anova) with SPSS. Results: Marital satisfaction significantly relates to sexual satisfaction (P= 0/00). There was also a significant relation between sexual satisfaction and the following variables: age difference of couples (P= 0.04), length of marital life (P= 0.05), and a drug abused participant (P= 0.007). Of these variables, only the age difference of couples significantly relates to marital satisfaction (0.00). Conclusion: Findings suggest that sexual satisfaction plays a seminal role in marital satisfaction of Iranians. Therefore, we need to develop culturally appropriate practical strategies to improve Iranian couples' awareness in sexuality issues as well as training them in communication skills through their sexual encounters.